2020
DOI: 10.46743/1540-580x/2020.1892
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Readiness Exam for Predicting Radiography Program Success: A Pilot Study

Abstract: Background: Research investigating predictors of academic success in rigorous health science education is valuable for curricular intervention for identified at-risk students. Various predictors of success have been investigated, but the literature is insufficient when examining anatomy and physiology readiness scores as they correlate to radiography curricular success. This pilot study assessed the correlation between readiness exam scores and programmatic course GPA to determine if the scores could be used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results reveal that there was no single selection method that was most frequently used; instead, different combinations of selection methods were used amongst the universities. 25,26,34 The results are in the line with previous studies which have identified a huge variety in radiography student selection methods. 6,7,9 This result may indicate that there is no common understanding of what should be assessed in radiography student selection.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results reveal that there was no single selection method that was most frequently used; instead, different combinations of selection methods were used amongst the universities. 25,26,34 The results are in the line with previous studies which have identified a huge variety in radiography student selection methods. 6,7,9 This result may indicate that there is no common understanding of what should be assessed in radiography student selection.…”
Section: Discussionsupporting
confidence: 90%
“…However, it needs to be noted that these results were based on three studies. 25,27,28 Moreover, the factors from the categories of personality traits, social skills, and career choice were not related to study success. The reason for this may be that there were only few studies that reported the assessment of these factors.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations